Long Journeys. African Migrants on the Road 2013
DOI: 10.1163/9789004250390_005
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Migration: From Senegal to the Canary Islands by Sea

Abstract: several years ago, european newspapers regularly published stories and pictures of West african men arriving dehydrated and exhausted on the touristy beaches of the Canary islands (bbC news 2006). Particularly alarming were the large number of deaths en route of migrants not fleeing war or persecution but in search of greener pastures (Ceesay 2007). although migration from West africa is not a new phenomenon the means and trends of migration have changed considerably over the past years, with most notably the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies have shown that colonial ties increase migration between colonisers and their former colonies because of common official language, business relations, cultural attachment, and/or social networks (Gimenez-Gomez, 2019). The EU has a stable political climate and a strong economic base, and the economic disparities between Africa and the EU are essential predictors of African migration flows (Poeze, 2010). Studies have shown that demand for labour is a way of establishing equilibrium between the sending countries that supply labour and the receiving countries where there are demands for labour.…”
Section: Economic Influence On Irregular Migrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that colonial ties increase migration between colonisers and their former colonies because of common official language, business relations, cultural attachment, and/or social networks (Gimenez-Gomez, 2019). The EU has a stable political climate and a strong economic base, and the economic disparities between Africa and the EU are essential predictors of African migration flows (Poeze, 2010). Studies have shown that demand for labour is a way of establishing equilibrium between the sending countries that supply labour and the receiving countries where there are demands for labour.…”
Section: Economic Influence On Irregular Migrationmentioning
confidence: 99%
“…Studies have shown that demand for labour is a way of establishing equilibrium between the sending countries that supply labour and the receiving countries where there are demands for labour. It is assumed that emigration will occur when there is a possibility of a good net return (Poeze, 2010). Applying the classical economic push-pull theory, it could be contended that migrants mainly respond to economic differences between the country of origin and the country of destination.…”
Section: Economic Influence On Irregular Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…These migration aspirations emerge, however, in times that the popular destination 'Europe' is doing its best efffort to keep out would-be immigrants originating from the global South. This leads to a widespread frustration among sub-Saharan Africans over their relative immobility (see for a Cape-Verdean case Carling (2002), for Malian cases Barten (2009) and Jóns-son (2008), and for Senegalese cases Poeze (2010) and Nyamnjoh (2010)). Partly because of this frustration, many migrants take the route of irregular migration in order to reach the EU (de Haas 2007).…”
Section: Introductionmentioning
confidence: 99%